Прагматика мотива и антропология «жизненного мира» - Bogdanov, Konstantin (Wiener Slawistischer Almanach, 2022)
Conceptual history as a scientific discipline (Begriffsgeschichte) confirms the long-standing observation that the acceptance of certain words as self-evident and widely used is not only semantically determined, but it also has an institutional and social dimension (Koselleck 1972: 116–131). Scientific concepts not only denote something, but also work as an instrument of group identification. Its establishment and maintenance is conditional and changeable. In various fields of knowledge, the same words can mean different things. Being context-specific, terms imply different semantic connections referring to a variety of pragmatic needs such as making statements, posing questions, expressing doubt, offering an explanation, etc. Ultimately, the nature of any interpretation is predetermined by its pragmatic aim and, therefore, alternative efforts (Albert 2003). This article is devoted to the concepts of motive and motivation in the contexts of their usage in the Russian language. It also has a certain revisionist theoretical agenda, suggesting the possibilities of a heuristic correlation of these concepts as a method of philological anthropology.